Gender transformative innovation: Women's inclusion in livestock vaccine systems in northern Ghana - Njiru, Nelly; Galiè, Alessandra; Omondi, Immaculate A.; Omia, Dalmas; Loriba, Agnes; Awin, Peter (Elsevier, 2024)
CONTEXT Owning livestock can support women's empowerment and progress toward gender-equitable agri-food systems. Gender inequality, however, can reduce women's ownership of livestock and access to animal vaccines. Gender accommodative approaches (GAAs), and more recently gender transformative approaches (GTAs), are increasingly implemented in development interventions. However, their impact on women's empowerment has not been systematically tested. Here, we describe the ‘Women Rear Project’, implemented in northern Ghana between 2019 and 2023, and assess the impact of GTAs and GAAs on women's empowerment, ownership of livestock, and access to animal vaccines.